2006
DOI: 10.1097/01.olq.0000187233.53622.8a
|View full text |Cite
|
Sign up to set email alerts
|

Gonorrhea Reinfection Among Sexually Transmitted Disease Clinic Attendees in Baltimore, Maryland

Abstract: Although reinfection rates were high, we found that field staff intervention to increase follow-up testing rates did not identify a significant amount of repeat infections compared with passive surveillance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 36 publications
2
14
0
1
Order By: Relevance
“…2,[43][44][45][46] Several studies that did not identify statistical significance still noted a trend of increased reinfection in younger participants. [47][48][49][50][51][52][53][54][55] The relationship between race or ethnicity and reinfection varied by study. Non-Hispanic blacks had a significantly higher risk of chlamydia reinfection in some studies; 2,37,39,42,44,46,56 however, other studies found no association with reinfection, 35,38,41,45,[57][58][59] despite a high proportion of black participants in several of these studies.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…2,[43][44][45][46] Several studies that did not identify statistical significance still noted a trend of increased reinfection in younger participants. [47][48][49][50][51][52][53][54][55] The relationship between race or ethnicity and reinfection varied by study. Non-Hispanic blacks had a significantly higher risk of chlamydia reinfection in some studies; 2,37,39,42,44,46,56 however, other studies found no association with reinfection, 35,38,41,45,[57][58][59] despite a high proportion of black participants in several of these studies.…”
Section: Resultsmentioning
confidence: 96%
“…37,40,42,44,50,56,60 Of the studies that did not find a statistically significant relationship between race and gonorrhea reinfection, 2 of 3 study populations were over 80% black. 36,47 Of the 8 studies that examined the role of coinfection on reinfection estimates, 6 identified a statistically significant association. Five studies demonstrated that coinfection with gonorrhea increased reinfection with chlamydia, 2,38 -39,46,61 and 3 studies demonstrated that coinfection with chlamydia increased the risk of gonorrhea reinfection.…”
Section: Resultsmentioning
confidence: 97%
“…12 It is important to note that retesting for repeat chlamydia infection is distinct from a ''test-of-cure,'' which is now routinely recommended only for pregnant women 4 to 6 weeks after treatment and is primarily aimed at detecting treatment failure, not repeat infection. Though national retesting guidelines have existed since 2002, retesting rates in various clinical settings remain low: 43% in Job Corps clinics, 13,14 15%-38% in STD clinics, [15][16][17] and 21%-25% in California family planning clinics. (H. Howard, 2009, personal communication).…”
Section: Introductionmentioning
confidence: 99%
“…(19) Repeat screening using NAAT testing six months after completing therapy is recommended for individuals at risk for reinfection. (20,21) Cotreatment for chlamydia is indicated for all patients with proven gonorrhea, even if chlamydia is not detected. Syphilis: All pregnant adolescents should be screened for syphilis early in pregnancy and, ideally, again at delivery.…”
Section: Box 1 Which Adolescents Should Be Screened For Sexually Tranmentioning
confidence: 99%